Low muscle strength and self-reported fatigue in patients on hemodialysis: findings from the SARC-HD study - Duarte, Marvery P.; Nóbrega, Otávio T.; Silva, Maryanne Z. C.; Mondini, Dario R.; Sant'Helena, Bruna M.; Bundchen, Daiana C.; Bohlke, Maristela; Adamoli, Angélica N.; Lima, Ricardo M.; Inda-Filho, Antônio; Viana, João L.; Vogt, Barbara P.; et al. (Frontiers in Nutrition, 2025)
BackgroundWhether low muscle strength contributes to fatigue remains poorly understood. We investigated the association between dynapenia and self-reported fatigue in patients on hemodialysis.MethodsA cross-sectional analysis of the multicenter SARC-HD study in 19 dialysis units across Brazil. Muscle strength was evaluated by handgrip strength (HGS) and five times sit-to-stand (STS-5). Low muscle strength (i.e., dynapenia) was defined based on the revised EWGSOP. Patients were stratified into four dynapenia phenotypes (i) no dynapenia; (ii) low HGS; (iii) low STS-5; and (iv) severe dynapenia (low HGS and STS-5). From the validated 36-item short-form health survey (SF-36) question about tiredness, patients self-reported their frequency of fatigue as (i) Never or rarely; (ii) Sometimes; and (iii) Always or constantly.ResultsAmong 841 patients (58 ± 15 years, 38% female, and 49% Black), the prevalences of dynapenia by low HGS, low STS-5, and severe dynapenia were 13.9, 18.8, and 12.1%, respectively. Frequency of fatigue, self-reported as “Never or rarely,” “Sometimes” or “Always or constantly” was 39.5, 30.3, and 30.2%, respectively. The frequency of “Always or constantly” feeling fatigued was 24.2% among patients without dynapenia, 36.5% in dynapenia by low HGS, 37.2% in dynapenia by low STS-5, and 37.8% in severe dynapenia (p < 0.001). Adjusted logistic regressions showed a significant association between all dynapenia phenotypes and high frequency of fatigue compared to those without dynapenia (low HGS: odds ratio [OR] = 1.91; 95% confidence intervals [CI]: 1.12–3.23; low STS-5: OR = 2.35; 95%CI: 1.50–3.69; severe dynapenia: OR = 2.73; 95%CI: 1.55–4.81).ConclusionPatients on hemodialysis with low muscle strength were more likely to self-report a higher frequency of fatigue, independently of the dynapenia phenotype. This highlights the importance of recognizing low muscle strength as a potential contributor to fatigue in this population.